2017
DOI: 10.1186/s13071-017-2571-0
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spp. biomass has increased in raccoon dogs (Nyctereutes procyonoides) and red foxes (Vulpes vulpes) in Estonia

Abstract: BackgroundRaccoon dogs and red foxes are well-adapted hosts for Trichinella spp. The aims of this study were to estimate Trichinella infection prevalence and biomass and to investigate which Trichinella species circulated in these indicator hosts in Estonia.MethodsFrom material collected for evaluating the effectiveness of oral vaccination program for rabies eradication in wildlife, samples from 113 raccoon dogs and 87 red foxes were included in this study. From each animal, 20 g of masseter muscle tissue was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
1
21
1
Order By: Relevance
“…T. spiralis , T. britovi , T. nativa and T. pseudospiralis , as single or mixed infection. However, the prevalence varies between different European regions, from 0% in Denmark and Austria, 1.9% and 4% in Germany, 28% and 33.2% in Finland, 29.3% and 32.5% in Lithuania, and 35.5% in Latvia, to 42% and 57.5% in Estonia (Malakauskas et al, 2007; Airas et al, 2010; Pannwitz et al, 2010; Bružinskaitė-Schmidhalter et al, 2011; Al-Sabi et al, 2013; Mayer-Scholl et al, 2016; Duscher et al, 2017; Kärssin et al, 2017; Antti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T. spiralis , T. britovi , T. nativa and T. pseudospiralis , as single or mixed infection. However, the prevalence varies between different European regions, from 0% in Denmark and Austria, 1.9% and 4% in Germany, 28% and 33.2% in Finland, 29.3% and 32.5% in Lithuania, and 35.5% in Latvia, to 42% and 57.5% in Estonia (Malakauskas et al, 2007; Airas et al, 2010; Pannwitz et al, 2010; Bružinskaitė-Schmidhalter et al, 2011; Al-Sabi et al, 2013; Mayer-Scholl et al, 2016; Duscher et al, 2017; Kärssin et al, 2017; Antti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, raccoon dogs from the Głęboki Bród Forest District tested in the present study were infected with T. britovi alone; this is not surprising as it is well documented that carnivorous mammals are preferential hosts for T. britovi (Pozio and Zarlenga, 2013). T. britovi infection has been described in 74% of raccoon dogs examined in Lithuania, and in 40.5% and 24.8% of tested individuals in Estonia (Malakauskas et al, 2007; Kärssin et al, 2017). In contrast, the most commonly-identified Trichinella species identified in raccoon dogs in Finland was T. nativa , followed by T. spiralis and T. britovi (Airas et al, 2010); this contrasts with Antti et al (2018) who found T. nativa to be prevalent among raccoon dogs in Finland, followed by T. britovi .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichinella spp. are endemic in wildlife in Estonia [ 6 ]. A high proportion, 42.1%, of investigated wild boars that were hunted in 2012–2013 tested positive for antibodies against Trichinella [ 7 ], and the biomass of Trichinella has increased in the main reservoir hosts raccoon dogs ( Nyctereutes procyonoides ) and red foxes ( Vulpes vulpes ) [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These hosts are native to East Asia and North America and have been introduced across Europe, including the Czech Republic, where they have spread zoonotic parasites and other pathogens (e.g. Echinococcus or Trichinella) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%